Characterization of the Chilean financial cycle, early warning indicators and implications for macro-prudential policies - Juan Francisco Martínez; Daniel Oda (Latin American Journal of Central Banking (LAJCB), 2021)
From the perspective of an emerging country - Chile - we analyze the recommendations of the Basel Committee of Banking Supervision (BCBS) regarding the design and implementation of indicators to guide countercyclical capital buffer (CCyB) policy decisions. We analyze the sensitivity of the predictive power to the calculation methodology of different early warning indicators (EWIs), including the standard credit-to-GDP gap. To meet these goals, we expand the available data of loans, using quarterly data from 1970 to 2017, which covers three financial fragility periods. Additionally, we adjust the methodologies according to the domestic financial structure and the excessive amplitude of past local episodes. Finally, we discuss some remaining challenges for the application of the CCyB in Chile.
Keywords: 330